Simply Java programming. - Deitel, Harvey M., 1945-; Deitel, Paul J., 1969-; Listfield, Jeffrey A., ....- (Upper Saddle River : Pearson, 2004)
For courses in Java-Intro to Programming/CS1, Java-Programming for Business; and Java/Visual J++-Introductory. Combining the Deitel signature Live-Code Approach with a new Application-Driven methodology, this text uses a step-by-step tutorial approach to begin teaching students the basics of programming, builds upon previously learned concepts, and introduces new programming features in each successive tutorial. This comprehensive introduction to Java covers GUI design, swing components, methods, classes, data types, control statements, arrays, object-oriented programming, strings and characters, sequential files, and more. It also includes higher-end topics such as database programming, multimedia and graphics, and Web applications development.
Keywords: Java (programmeertaal).